Pro iOS apps performance optimization - Vo, Khang (Apress, 2011)
Today's iPhone and iPad apps developers are often running into the need to refine, improve and optimize their apps performances. As more complex apps can be created, it is even more important for developers to deal with this critical issue. Pro iOS Apps Performance Tuning and Optimization covers many common but difficult problems when tuning and optimizing performance for iPhone and iPad apps and how to resolve these problems efficiently. This book gives you the following: Basic knowledge on common problems in iPhone apps Advanced knowledge over data structure, algorithms, multithreading, and network data in iPhone apps Comparison with problems and solutions for Android and Windows Phone apps After reading this must-have book, you'll be ready to make the most of the processing power of the iPhone with your apps performance optimization know-how.